FACTORS CAUSING FOREIGN LANGUAGE ANXIETY (FLA) IN SPEAKING - Alheru Akbar; Dedi Sofyan; Indah Damayanti (Universitas Bengkulu, 2018)
This research attempted to find out the factors causing foreign language anxiety in speaking. This research was carried out by employing descriptive quantitative design. The population of this research was the third semester students of English Education Study Program of University of Bengkulu in academic year 2017/2018. The samples of this research were taken by using total sampling tehcnique, i.e 79 students. The data were collected by questionnaire consisted of 29questions related to the anxiety. The results of this study showed that the students mostly had the anxiety. There were three factors that causing the anxiety of the students in speaking; Test Anxiety (Mildly Affected; Mean Score: 3.09), Fear of Negative Evaluation (Mildly Affected;Mean Score: 3.00), and Communication Apprehension (Mildly Affected; Mean Score: 2.90). In conclusion, there were three factors that causing the student’ anxiety in speaking, and the most dominant factors is the Test Anxiety. In addition, from the test anxiety, it was found that mostly students were afraid of the consequences failing their speaking class